Potential of bioremediation and PGP traits in Streptomyces as strategies for bio-reclamation of salt-affected soils for agriculture - Romano-Armada, Neli (2021)
Environmental limitations influence food production and distribution, adding up to global problems like world hunger. Conditions caused by climate change require global efforts to be improved, but others like soil degradation demand local management. For many years, saline soils were not a problem; indeed, natural salinity shaped different biomes around the world. However, overall saline soils present adverse conditions for plant growth, which then translate into limitations for agriculture. Shortage on the surface of productive land, either due to depletion of arable land or to soil degradation, represents a threat to the growing worldwide population. Hence, the need to use degraded land leads scientists to think of recovery alternatives. In the case of salt-affected soils (naturally occurring or human-made), which are traditionally washed or amended with calcium salts, bio-reclamation via microbiome presents itself as an innovative and environmentally friendly option. Due to their low pathogenicity, endurance to adverse environmental conditions, and production of a wide variety of secondary metabolic compounds, members of the genus Streptomyces are good candidates for bio-reclamation of salt-affected soils. Thus, plant growth promotion and soil bioremediation strategies combine to overcome biotic and abiotic stressors, providing green management options for agriculture in the near future.